The 5th International Conference on Virtual and Augmented Reality in Education 2019
DOI: 10.46354/i3m.2019.vare.002
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality - A curatorial tool

Abstract: "The flood of information in today’s society makes it difficult for undergraduate students to source quality support materials to help in their study, as many are illequipped to distinguish the good from the bad. Because of this, the lecturer’s role as curator of learning resources has developed and become a vital aspect of their job. It is no longer sufficient simply to provide reading lists. As more and more content of various levels of quality has become available online, some lecturers have taken it upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Personal audio guides typically utilise spoken descriptions of cultural content to offer augmented-reality-enhanced tourist experiences [30]. Verbal description of points of interest can not only refer to the real world but also represent in detail a fictional world, such as the medieval setting with mages and monsters in [31].…”
Section: Speech In Ag Designmentioning
confidence: 99%
“…Personal audio guides typically utilise spoken descriptions of cultural content to offer augmented-reality-enhanced tourist experiences [30]. Verbal description of points of interest can not only refer to the real world but also represent in detail a fictional world, such as the medieval setting with mages and monsters in [31].…”
Section: Speech In Ag Designmentioning
confidence: 99%
“…Two decades ago, Sawhney et al Sawhney and Schmandt [2000] harnessed audio information to keep users of wearable devices updated with incoming messages and events. Lyons et al Lyons et al [2000] developed an AR game system named "Guided by Voices", which equipped the user with a narrative sound clip that indicated the scenarios encountered and the correct steps to be taken for proceeding. Interestingly and more recently, Mulloni et al Mulloni et al [2011] found that AR can be integrated with a mobile navigation system, while audio hints can be advisable for eye-free usage.…”
Section: Hints In Armentioning
confidence: 99%
“…Another well-adopted hint is the audio hint, which presented as voice commands or directives can swiftly and clearly aid the user. A number of researchers have exploited audio hints for the purpose of informing, guiding, and directing within their designs Lyons et al [2000], Sawhney and Schmandt [2000]. However, even though there is a substantial body of research into how visual and audio hints work in AR tasks, little has focused on search tasks other than exploring the combination of visual and audio hints in one AR framework.…”
Section: Introductionmentioning
confidence: 99%
“…AR can be displayed on different types of hardware, such as immersive headsets (Frydenberg et al, 2021) and fixed displays (Oh et al, 2016). Often, the virtual features are visual; in some cases, other senses are also involved, such as hearing (Lyons et al, 2000). A well-designed, usable AR interface could increase SA (Wickens, 2008).…”
Section: Ar For Ship Navigationmentioning
confidence: 99%